2011
DOI: 10.2147/jmdh.s14949
|View full text |Cite
|
Sign up to set email alerts
|

Preconceptions and expectations of older adults about getting hearing aids

Abstract: Aim:The objectives of this study were to describe preconceptions and expectations of older adults about getting hearing aids and to explore the influence of hearing loss (HL), hearing aid experience, gender, age, and marital status on these preconceptions and expectations.Methods:A total of 174 participants aged above 65 years were randomly selected from a waiting list for hearing aid fitting. Hearing threshold was tested using pure tone audiometry. A self-report questionnaire with a specific focus on preconce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
1
9
0
1
Order By: Relevance
“…Hearing-aid use was directly related to the severity of measured HI, with the highest utilization in men and women with more severe hearing loss, consistent with earlier studies (Chien & Lin, 2012; Lee et al, 1991; Popelka et al, 1998; Gopinath et al, 2011; Nash et al, 2013). In multivariable analyses, age was not a significant factor, whereas severity of measured hearing loss and perception of hearing ability were the most consistent and significant factors associated with hearing-aid use in men and in women, corroborating results from community-based studies and targeted investigations probing help-seeking factors in hearing-impaired individuals (Hartley et al, 2010; Gopinath et al, 2011; Garstecki & Erler, 1998; Southall, Gagne & Leroux, 2006; Solheim, 2011; Meyer et al, 2014; Laplante-Levesque et al, 2012). …”
Section: Discussionsupporting
confidence: 68%
“…Hearing-aid use was directly related to the severity of measured HI, with the highest utilization in men and women with more severe hearing loss, consistent with earlier studies (Chien & Lin, 2012; Lee et al, 1991; Popelka et al, 1998; Gopinath et al, 2011; Nash et al, 2013). In multivariable analyses, age was not a significant factor, whereas severity of measured hearing loss and perception of hearing ability were the most consistent and significant factors associated with hearing-aid use in men and in women, corroborating results from community-based studies and targeted investigations probing help-seeking factors in hearing-impaired individuals (Hartley et al, 2010; Gopinath et al, 2011; Garstecki & Erler, 1998; Southall, Gagne & Leroux, 2006; Solheim, 2011; Meyer et al, 2014; Laplante-Levesque et al, 2012). …”
Section: Discussionsupporting
confidence: 68%
“…In einer Studie aus Norwegen wurden 174 Patienten einer Warteliste von 193 Personen für Hörgeräteanpassung nach ihren Erwartungen in Bezug auf die Hörgeräte gefragt [39]. Die Patienten waren alle älter als 65 Jahre.…”
Section: Nebeneffekte Des Tragens Von Hörgeräten: Schwitzen Und Cerumunclassified
“… 22 A study suggested that less-positive expectations and more problem-oriented preconceptions among subjects with mild hearing loss might explain why hearing aids are used scarcely. 23 Such attitudes and expectations of people with hearing loss may have been formed by various societal factors, such as exposure to media and information found on the Internet. 24 …”
Section: Introductionmentioning
confidence: 99%